A silicon-based negative electrode material for sulfide solid-state lithium battery and its application

By using composite negative electrode materials in sulfide solid lithium batteries, combined with silicon, electrolyte, lithium alloy lithium supplement agent and metal nanoparticles, the problems of silicon negative electrode volume expansion and low conductivity are solved, and the rate performance and Coulomb efficiency of the battery are improved.

CN119230811BActive Publication Date: 2025-04-15SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411774600.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-15
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

In sulfide solid lithium batteries, the volume expansion rate of the silicon negative electrode during charging and discharging is high, resulting in a decrease in battery efficiency, a sharp drop in capacity, and a low electronic conductivity, affecting the rate performance.

Method used

The composite negative electrode material is used, consisting of silicon, electrolyte, lithium alloy lithium supplement agent and metal nanoparticles. It is evenly mixed by ball milling to improve the electron conductivity and ionic conductivity and avoid side reactions caused by conductive carbon.

Benefits of technology

It effectively suppresses the volume expansion of the silicon negative electrode, improves the rate performance and Coulomb efficiency of the whole battery, and promotes the improvement of battery capacity and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230811B_ABST
    Figure CN119230811B_ABST
Patent Text Reader

Abstract

The present invention relates to a silicon-based negative electrode material for a sulfide solid-state lithium battery, which is prepared by the following method: mixing silicon powder with a sulfide solid electrolyte and ball milling, then adding a lithium alloy lithium supplement, and continuing ball milling to obtain a mixed powder; then uniformly mixing the mixed powder with metal nanoparticles to obtain the silicon-based negative electrode material, which can simultaneously improve the electronic conductivity and ionic conductivity of the silicon negative electrode. The lithium supplement of the present invention selects a lithium alloy material, which has good compatibility with the sulfide electrolyte, and can effectively suppress the volume expansion coefficient of the silicon negative electrode after addition; secondly, with the simultaneous improvement of the negative electrode electronic conductivity and ionic conductivity, the rate and coulomb efficiency of the whole battery will be comprehensively improved, and the negative electrode interface stability limit will be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium batteries, and in particular relates to a silicon-based negative electrode material for a sulfide solid-state lithium battery and an application thereof. Background Art

[0002] New energy is replacing traditional oil vehicles with an unstoppable momentum and becoming a new force in car manufacturing. Therefore, the commercial application and technological innovation of lithium-ion batteries are facing unprecedented opportunities and challenges, which are mainly limited by the safety and energy density of liquid lithium batteries. At present, the ionic conductivity of sulfide solid electrolytes has reached / surpassed that of liquid electrolytes, and it is one of the most promising all-solid-state lithium battery technology routes. However, the high activity of sulfide solid electrolytes determines that its stability at the positive and negative electrode interfaces is greatly limited during the charging and discharging process. Among them, the main problems at the negative electrode / sulfide solid electrolyte interface are: ① During the discharge process, the reduction products of the sulfide solid electrolyte limit the transmission of lithium ions at the interface; ② Incomplete contact of the solid-solid interface leads to side reactions at the interface; ③ Microscopic defects at the negative electrode interface induce uneven deposition of lithium ions, leading to the formation and growth of lithium dendrites.

[0003] Although lithium metal is the holy grail of lithium-ion batteries, the direct use of lithium metal as the negative electrode in contact with the sulfide solid electrolyte can easily lead to the formation of lithium dendrites, which eventually causes the battery to short-circuit. Silicon negative electrode is an excellent choice for lithium-ion battery negative electrode due to its high specific capacity (4200mAh / g), which helps to improve the energy density of the battery. However, the volume expansion rate of pure silicon negative electrode exceeds 300% when fully charged, and the coulombic efficiency of the battery is reduced, which eventually leads to a sharp drop in battery capacity. In addition, silicon is a semiconductor material, and its low electronic conductivity leads to low rate performance of the whole battery. This patent provides a method for preparing a silicon-based negative electrode for sulfide all-solid-state lithium battery, which is intended to simultaneously improve the electronic conductivity and ionic conductivity of the silicon negative electrode, solve the volume expansion problem of the silicon negative electrode, improve the rate performance and coulombic efficiency of the whole battery, and significantly improve the capacity and cycle stability of the battery, providing important ideas for the commercial application of sulfide all-solid-state lithium batteries. Summary of the invention

[0004] The purpose of the present invention is to provide a silicon-based negative electrode material for sulfide solid-state lithium batteries and its application in view of the problems existing in the prior art.

[0005] Conventional silicon-based negative electrode materials include silicon, electrolyte, and conductive carbon, but at the negative electrode / sulfide solid electrolyte interface, conductive carbon causes the sulfide electrolyte to decompose, resulting in side reactions at the negative electrode interface, and the generated products inhibit lithium ion transmission. If there is an electrolyte in the negative electrode itself, the conductive carbon will also cause the electrolyte in the negative electrode to be reduced and decomposed. The composite negative electrode of the present invention is composed of silicon, electrolyte, lithium alloy (lithium supplement agent), and metal powder (electronic conductive agent). The present invention uses metal powder as a conductive agent without the addition of conductive carbon, and the above problems do not exist. Adding a lithium supplement agent to the negative electrode not only improves the ionic conductivity of the negative electrode, but also improves its electronic conductivity. At the same time, the lithium alloy material consistent with the added metal powder is conducive to improving the reversibility of lithium ion alloying / de-alloying of the composite negative electrode during the charge and discharge process.

[0006] The purpose of the present invention can be achieved by the following scheme:

[0007] In a first aspect, the present invention provides a silicon-based negative electrode material for a sulfide solid-state lithium battery, which is prepared by the following method:

[0008] S1, mixing silicon powder and sulfide solid electrolyte and ball milling, then adding lithium alloy lithium supplement agent, and continuing ball milling to obtain mixed powder;

[0009] S2, uniformly mixing the mixed powder with metal nanoparticles (metal conductive agent corresponding to lithium alloy) to obtain the silicon-based negative electrode material;

[0010] The metal nanoparticles are the same as the metal that forms an alloy with lithium in the lithium alloy supplement.

[0011] As an embodiment of the present invention, in step S1, the sulfide solid electrolyte includes Li7P3S 11 , Li 10 GeP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 、Li6PS5Br、Li6PS5I、Li 11 Si2PS 12 , Li 10 SnP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 6.6 Ge 0.6 P 0.4 One or more of S5I.

[0012] As an embodiment of the present invention, in step S1, the particle size of the silicon powder is in the range of 20 nm-10 μm. If the particle size is not in the range, the particle contact of the composite negative electrode material is affected and ion conduction is inhibited.

[0013] The sulfide solid electrolyte used in the present invention is soft and difficult to disperse. The purpose of mixing silicon powder and electrolyte first is to improve the uniform mixing of multiple materials of the composite negative electrode. If it is added simultaneously with lithium alloy lithium supplement and metal nanoparticles, the sulfide solid electrolyte is prone to agglomeration, and the electronic and ionic conductive networks of the composite negative electrode are uneven, which is not easy to uniformly deposit lithium ions.

[0014] As an embodiment of the present invention, in step S1, the mass ratio of silicon powder to sulfide solid electrolyte is (60-95): (5-40).

[0015] As an embodiment of the present invention, in step S1, the parameters of the ball milling are: rotation speed range is 300-550rpm, ball milling time is 2-4h; ball to material ratio is (5-20):1.

[0016] As an embodiment of the present invention, in step S1, the lithium alloy supplement includes one of the alloys formed by lithium and metal M, and the metal M includes one of Ag, Al, Sn, Mg, and Zn. The alloy includes Li 10 Ag3, Li9Ag4, LiAg, LiAl, Li3Al2, Li9Al4, L 13 Sn4, Li3Sn, Li 15 Sn4, Li4Sn, Li 4.25 Sn、Li 22 One of Sn5, LiMg, and LiZn. Adding a lithium supplement agent helps the negative electrode material to de-alloy during the discharge process and improves the coulombic efficiency during the charge and discharge process. During the lithium ion transmission process, the generation of "dead lithium" is inevitable at the positive and negative electrode interfaces, resulting in the attenuation and loss of battery capacity. The lithium supplement agent can effectively supplement the battery capacity and improve the long-cycle stability of the whole battery. At the same time, the alloys involved in the present invention are all consistent with the metal M, and the lithium supplement agent can also act as an electronic conductive agent to a certain extent, effectively avoiding the generation of more than two lithium alloys during the negative electrode lithium insertion process, and the structure is uncontrolled.

[0017] As an embodiment of the present invention, in step S1, the mass ratio of the lithium alloy lithium supplement agent to the silicon powder is (5-20): (80-95).

[0018] As an embodiment of the present invention, in step S1, the ball milling parameters of the continued ball milling are: a rotation speed range of 300-550 rpm, a ball milling time of 2-4 h; and a ball-to-material ratio of (5-20):1.

[0019] As an embodiment of the present invention, in step S2, the metal nanoparticles include one of metal Ag, Al, Sn, Mg, and Zn, which is consistent with the metal M in the lithium alloy lithium supplement. The silicon-based negative electrode material of the present invention does not contain conductive carbon. In addition to being a conductive agent, the metal nanoparticles improve the electronic conductivity of the negative electrode, and can also be used as a lithium storage material to receive lithium ions during the charging process, promote the occurrence of lithium ion alloying, and form an alloy, which not only improves the capacity of the negative electrode, but also does not reduce the energy density of the all-solid-state lithium battery. More importantly, it avoids the direct deposition of lithium at the negative electrode / electrolyte interface, and acts as a metal stabilizing framework, thereby effectively avoiding the formation and growth of lithium dendrites and effectively inhibiting the volume expansion of the silicon negative electrode. If metal nanoparticles are not added, the electronic conductivity is poor, and the capacity, cycle stability and rate performance of the battery will be greatly affected.

[0020] As an embodiment of the present invention, in step S2, the particle size of the metal nanoparticles is in the range of 5-500 nm. If the particle size is not in the range, the particle contact of the composite negative electrode material is affected and ion conduction is inhibited. When mixing, the mixed powder and the metal nanoparticles are ground evenly.

[0021] As an embodiment of the present invention, in step S2, the weight ratio of the metal nanoparticles to the silicon powder is (10-30): (70-90).

[0022] In a second aspect, the present invention also provides a silicon-based negative electrode, which is a dry or wet negative electrode plate prepared from the silicon-based negative electrode material. The dry negative electrode plate is prepared by mixing the silicon-based negative electrode material with a dry adhesive; the wet negative electrode plate is prepared by mixing the silicon-based negative electrode material with a dry adhesive and a solvent.

[0023] As an embodiment of the present invention, the dry process adhesive used for the dry process negative electrode plate includes one or more of PTFE and PVDF.

[0024] As one embodiment of the present invention, the wet process adhesive used for the wet process negative electrode plate includes one or more of methyl cellulose, polytetrafluoroethylene, hydroxypropyl methyl cellulose, ethyl cellulose, polybutadiene block copolymer rubber, polyvinylidene fluoride, and the like.

[0025] As an embodiment of the present invention, the solvent used for the wet-process negative electrode plate includes one or more of toluene, ethanol, isopropanol, xylene, n-heptane, hexyl butyrate, NMP, and the like.

[0026] As an embodiment of the present invention, the mass ratio of the binder to the silicon-based negative electrode material in the dry or wet negative electrode sheet is (0.4-8):100.

[0027] In a third aspect, the present invention further provides a sulfide solid-state lithium battery, comprising the silicon-based negative electrode, a sulfide solid-state electrolyte, and a composite positive electrode material.

[0028] As an embodiment of the present invention, the sulfide solid electrolyte is consistent with the sulfide solid electrolyte used in the silicon-based negative electrode.

[0029] As an embodiment of the present invention, the composite positive electrode material includes a positive electrode active material, a sulfide solid electrolyte, and conductive carbon.

[0030] The positive electrode active material includes one or more of ternary positive electrode materials, lithium cobalt oxide, sulfur, and metal sulfide.

[0031] The ternary positive electrode materials include one or more of NCM111, NCM424, NCM523, NCM622, NCM811, NCM90, and NCM95.

[0032] The metal sulfide includes one or more of Fe2S, MoS2, TiS2, and NiS.

[0033] Sulfide solid electrolytes include Li7P3S 11 , Li 10 GeP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 、Li6PS5Br、Li6PS5I、Li 11 Si2PS 12 , Li 10 SnP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 6.6 Ge 0.6 P 0.4 One or more of S5I.

[0034] The conductive carbon includes one of acetylene black, VGCF, graphene, and Super P.

[0035] As an embodiment of the present invention, the sulfide solid electrolyte is consistent with the sulfide solid electrolyte used in the silicon-based negative electrode.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The silicon negative electrode has the problem of volume expansion, which brings about the coulombic efficiency and negative electrode interface stability problems of sulfide all-solid-state lithium batteries. Different from the material system of the previous silicon-carbon negative electrode, the electronic conductivity enhancer of the present invention is metal nanoparticles; by adding a lithium supplement and a small amount of electrolyte at the same time, the ion conductivity is improved.

[0038] (2) The lithium supplement agent of the present invention is made of lithium alloy material, which has good compatibility with sulfide electrolyte and can effectively inhibit the volume expansion coefficient of the silicon negative electrode after addition; secondly, with the simultaneous improvement of the electronic conductivity and ionic conductivity of the negative electrode, the rate and coulombic efficiency of the whole battery will be comprehensively improved, and the negative electrode interface stability limit will be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0040] Figure 1 The EDS analysis results of the silicon-based negative electrode material prepared in Example 1, wherein the upper figure is the SEM image of the composite negative electrode, and the lower figure is the EDS test result of the composite negative electrode;

[0041] Figure 2 It is a comparison curve of rate performance test of full battery of Example 1 and Comparative Example 1;

[0042] Figure 3 It is a comparison curve of rate performance test of full battery of Example 2 and Comparative Example 2;

[0043] Figure 4 The charge and discharge comparison curves of the full battery of Example 1 and Comparative Example 3 at the 1st and 500th cycles;

[0044] Figure 5 This is the first cycle charging curve of the full battery of comparative example 4;

[0045] Figure 6 This is the charge and discharge curve of the first cycle of the full battery of comparative example 5;

[0046] Figure 7 The first cycle charge and discharge comparison curves of the full battery of Example 1, Comparative Example 6 and Comparative Example 7;

[0047] Figure 8 It is a specific capacity diagram of Example 1, Comparative Examples 8 and 9. DETAILED DESCRIPTION

[0048] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.

[0049] Example 1

[0050] This embodiment provides a silicon-based negative electrode, which is prepared by the following method (dry method):

[0051] 1) In a glove box filled with argon, weigh 700 mg of silicon (particle size 3-4 μm) and 300 mg of Li 10 GeP2S 12 The solid electrolyte was placed in a 100 mL zirconia ball milling jar, and 8 g of zirconia ball milling beads were weighed for high-energy ball milling. The ball milling parameters were 450 rpm and the ball milling time was 3 h.

[0052] 2) In a glove box filled with argon, place 200 mg of LiAl alloy in the ball milling jar prepared in step 1) and continue ball milling. The ball milling parameters are the same as those in step 1);

[0053] 3) Place the ball mill in a glove box filled with argon, place the mixed powder in a mortar, weigh 200 mg of Al powder with a particle size of 50 nm and place it in the mortar. After grinding evenly, the silicon-based negative electrode material is obtained.

[0054] 4) In a glove box filled with argon, weigh 100 mg of the silicon-based negative electrode material and 4 mg of PTFE powder in step 3), grind them in a mortar until the powder has a dough texture, then roll it with a stainless steel column to a thickness of 60 μm, and cut it into 10 mm diameter discs, which are silicon-based negative electrode sheets;

[0055] 5) Prepare the composite positive electrode: weigh 75 mg NCM811 powder, 22 mg Li 5.5 PS 4.5 Cl 1.5 The electrolyte powder and 3 mg VGCF powder were placed in a mortar and ground for 30 min until the powders were evenly mixed and set aside.

[0056] 6) Assemble the pressure cell: In a glove box filled with argon, weigh 40 mg of Li 5.5 PS 4.5 Cl 1.5The electrolyte powder was placed in a pressure battery mold with a diameter of 10 mm, and the electrolyte powder was rotated and flattened by rotating the stainless steel column, and pressed into tablets on a tablet press at a pressure of 120 MPa for 2 min. 40 mg of the Li 5.5 PS 4.5 Cl 1.5 The surface of the electrolyte sheet was flattened and pressed into a sheet on a sheet press at a pressure of 360 MPa for 2 min. A 10 mm diameter Al foil was placed on the surface of the composite positive electrode sheet as the positive electrode current collector. 5.5 PS 4.5 Cl 1.5 The disc cut in step 4) is placed on the other side of the electrolyte sheet, and the negative electrode current collector is Cu foil. After assembly, a pressure of 50 MPa is applied to obtain a sulfide all-solid-state lithium-ion battery.

[0057] Example 2

[0058] This embodiment provides a silicon-based negative electrode, which is prepared by the following method (wet method):

[0059] 1) In a glove box filled with argon, weigh 800 mg of silicon (particle size 3-4 μm) and 200 mg of Li6PS5Cl solid electrolyte and place them in a 100 mL zirconia ball milling jar, then weigh 10 g of zirconia ball milling beads and perform high-energy ball milling at 500 rpm for 3 h;

[0060] 2) In a glove box filled with argon, place 180 mg of LiAg alloy in the ball milling jar prepared in step 1) and continue ball milling. The ball milling parameters are the same as those in step 1);

[0061] 3) Place the ball mill in a glove box filled with argon, place the mixed powder in a mortar, weigh 200 mg of Ag powder with a particle size of 500 nm and place it in the mortar. After grinding evenly, the silicon-based negative electrode material is obtained. The EDS analysis results are as follows: Figure 1 As shown;

[0062] 4) Weigh 100 mg of the silicon-based negative electrode material obtained in step 3) and dissolve it in 100 mg of toluene solution containing 4% polybutadiene block copolymer rubber and place it in a 100 mL zirconia ball mill jar, add 1 g of zirconia ball mill beads, seal it and perform ball milling at 400 rpm for 4 h to obtain a silicon-based negative electrode slurry, which is coated on a Cu foil current collector with a coating thickness of 50 μm to obtain a wet-process negative electrode sheet.

[0063] 5) Prepare the composite positive electrode: weigh 75 mg NCM811 powder, 22 mg Li 5.5 PS 4.5 Cl 1.5The electrolyte powder and 3 mg VGCF powder were placed in a mortar and ground for 30 min until the powders were evenly mixed and set aside.

[0064] 6) Assemble the pressure cell: In a glove box filled with argon, weigh 40 mg of Li 5.5 PS 4.5 Cl 1.5 The electrolyte powder was placed in a pressure battery mold with a diameter of 10 mm, and the electrolyte powder was rotated and flattened by rotating the stainless steel column, and pressed into tablets on a tablet press at a pressure of 120 MPa for 2 min. 40 mg of the Li 5.5 PS 4.5 Cl 1.5 The surface of the electrolyte sheet was flattened and pressed into a sheet on a sheet press at a pressure of 360 MPa for 2 min. A 10 mm diameter Al foil was placed on the surface of the composite positive electrode sheet as the positive electrode current collector. 5.5 PS 4.5 Cl 1.5 The wet-process negative electrode disc cut in step 4) is placed on the other side of the electrolyte sheet. After assembly, a pressure of 50 MPa is applied to obtain a sulfide all-solid-state lithium-ion battery.

[0065] Comparative Example 1

[0066] The difference from Example 1 is that the negative electrode is directly pressed into sheets using 60 μm silicon powder, and the remaining steps are the same to obtain a sulfide all-solid-state lithium-ion battery.

[0067] Comparative Example 2

[0068] The difference from Example 2 is that the wet negative electrode slurry is a silicon negative electrode (silicon powder), and the remaining steps are the same to obtain a sulfide all-solid-state lithium-ion battery.

[0069] Comparative Example 3

[0070] The difference from Example 1 is that: in step 2), LiAl alloy is not added, in step 3), 400 mg Al powder is added, and the remaining steps are the same to obtain a sulfide all-solid-state lithium-ion battery.

[0071] Comparative Example 4

[0072] The difference from Example 1 is that: in step 3), Al powder is not added, in step 2), 400 mg of LiAl alloy is added, and the remaining steps are the same to obtain a sulfide all-solid-state lithium-ion battery.

[0073] Comparative Example 5

[0074] The difference from Example 1 is that Al powder is replaced by Fe powder, and the remaining steps are the same to obtain a sulfide all-solid-state lithium-ion battery.

[0075] Comparative Example 6

[0076] The difference from Example 1 is that Al powder is replaced with VGCF, and the remaining steps are the same to obtain a sulfide all-solid-state lithium-ion battery.

[0077] Comparative Example 7

[0078] The difference from Example 1 is that silicon powder, sulfide solid electrolyte, lithium alloy lithium supplement and metal nanoparticles are directly mixed and ball-milled.

[0079] Comparative Example 8

[0080] The difference from Example 1 is that the LiAl alloy is replaced by the LiSi alloy, and the other steps are the same to obtain a sulfide all-solid-state lithium-ion battery. The lithium-silicon alloy will have obvious volume expansion during the charge and discharge process.

[0081] Comparative Example 9

[0082] The difference from Example 1 is that Al powder is replaced by Zn powder, and the remaining steps are the same to obtain a sulfide all-solid-state lithium-ion battery.

[0083] Performance Testing

[0084] The sulfide all-solid-state lithium-ion battery was tested using the Xinwei battery testing system, equipment model: CT-4000, using a 0.1C-0.3C-1C-2C-0.1C rate charge and discharge process to test the discharge capacity of the sulfide all-solid-state lithium-ion battery. Figure 2-8 shown.

[0085] The discharge capacity of Example 1 at 0.1C rate is 195.08mAh / g, the discharge capacity at 0.3C rate is 179.2mAh / g, the discharge capacity at 1C rate is 168.01mAh / g, the discharge capacity at 2C rate is 151.02mAh / g, and the discharge capacity at 0.1C rate is 196.01mAh / g. The discharge capacity of Comparative Example 1 at 0.1C rate is 193.95mAh / g, the discharge capacity at 0.3C rate is 160.04mAh / g, the discharge capacity at 1C rate is 128.17mAh / g, the discharge capacity at 2C rate is 96.8mAh / g, and the discharge capacity at 0.1C rate is 192.05mAh / g.

[0086] The discharge capacity of Example 2 at a rate of 0.1C is 201.42 mAh / g, and the first-cycle coulomb efficiency is 83.12%; the discharge capacity of Comparative Example 2 at a rate of 0.1C is 171.2 mAh / g, and the first-cycle coulomb efficiency is 72.68%.

[0087] The discharge capacity of Example 1 at a rate of 0.08C is 200.95 mAh / g, and the first-cycle coulomb efficiency is 84.15%. After 500 cycles, the discharge capacity is reduced to 192.36 mAh / g, and the capacity retention rate is 95.38%; the discharge capacity of Comparative Example 3 at a rate of 0.08C is 195.75 mAh / g, and the first-cycle coulomb efficiency is 83.60%. After 500 cycles, the discharge capacity is reduced to 183.8 mAh / g, and the capacity retention rate is 93.89%.

[0088] Comparative Example 4 short-circuited when charged at a rate of 0.1C.

[0089] The discharge capacity of Comparative Example 5 at a rate of 0.1C is 156.54 mAh / g, and the first-cycle coulombic efficiency is 61.95%.

[0090] The discharge capacity of Comparative Example 6 at a rate of 0.08C is 199.13 mAh / g, and the first-cycle coulombic efficiency is 80.54%. During the first-cycle charging process, the electrolyte decomposes when the voltage is 3.3-3.5 V, and obvious side reactions occur.

[0091] The discharge capacity of Comparative Example 7 at a rate of 0.08C is 173.1 mAh / g, and the first-cycle coulombic efficiency is 80.08%.

[0092] The discharge capacity of Example 1 at 5C is 87.2 mAh / g, and the capacity decays to 82.8 mAh / g after 30 cycles, with a capacity retention rate of 94.95%; the discharge capacity of Comparative Example 8 at 5C is 84.7 mAh / g, and the capacity decays to 66.3 mAh / g after 30 cycles, with a capacity retention rate of 78.28%; the discharge capacity of Comparative Example 9 at 5C is 83.6 mAh / g, and the capacity decays to 75.8 mAh / g after 30 cycles, with a capacity retention rate of 90.67%.

[0093] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A silicon-based negative electrode material for a sulfide solid-state lithium battery, characterized in that: Prepared by a method comprising the steps of: S1, mixing silicon powder and sulfide solid electrolyte and ball milling, then adding lithium alloy lithium supplement agent, and continuing ball milling to obtain mixed powder; S2, uniformly mixing the mixed powder and the metal nanoparticles to obtain the silicon-based negative electrode material; In step S1, the lithium alloy lithium supplement includes one of the alloys formed by lithium and metal M, and the metal M includes one of Ag, Al, Sn, Mg, and Zn; The metal nanoparticles are the same as the metal that forms an alloy with lithium in the lithium alloy supplement; The silicon-based negative electrode material does not contain conductive carbon.

2. The silicon-based negative electrode material according to claim 1, characterized in that: In step S1, the sulfide solid electrolyte includes Li7P3S 11 , Li 10 GeP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 、Li6PS5Cl、Li 5.5 PS 4.5 Cl 1.5 、Li6PS5Br、Li6PS5I、Li 11 Si2PS 12 , Li 10 SnP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 6.6 Ge 0.6 P 0.4 One or more of S5I.

3. The silicon-based negative electrode material according to claim 1, characterized in that: In step S1, the particle size of the silicon powder is in the range of 20 nm to 10 μm; And / or, the particle size of the metal nanoparticles is in the range of 5-500 nm.

4. The silicon-based negative electrode material according to claim 1, characterized in that: In step S1, the mass ratio of silicon powder to sulfide solid electrolyte is (60-95): (5-40); And / or, the mass ratio of the lithium alloy lithium supplement agent to the silicon powder is (5-20): (80-95); And / or, the mass ratio of the metal nanoparticles to the silicon powder is (10-30): (70-90).

5. The silicon-based negative electrode material according to claim 1, characterized in that: In step S1, the parameters of the ball milling are: a rotation speed range of 300-550 rpm, and a ball milling time of 2-4 h; And / or, the ball milling parameters of the continued ball milling are: a rotation speed range of 300-550 rpm, and a ball milling time of 2-4 h.

6. A silicon-based negative electrode, characterized in that: The silicon-based negative electrode is a dry or wet negative electrode sheet prepared from the silicon-based negative electrode material according to claim 1.

7. The silicon-based negative electrode according to claim 6, characterized in that: The dry adhesive used for the dry negative electrode plate includes one or more of PTFE and PVDF; And / or, the wet process adhesive used for the wet process negative electrode plate includes one or more of methyl cellulose, polytetrafluoroethylene, hydroxypropyl methyl cellulose, ethyl cellulose, polybutadiene block copolymer rubber, and polyvinylidene fluoride; And / or, the solvent used for the wet-process negative electrode plate includes one or more of toluene, ethanol, isopropanol, xylene, n-heptane, hexyl butyrate, and NMP.

8. The silicon-based negative electrode according to claim 7, characterized in that: The mass ratio of the adhesive and the silicon-based negative electrode material in the dry or wet negative electrode sheet is (0.4-8):

100.

9. A sulfide solid-state lithium battery, characterized in that: It comprises the silicon-based negative electrode, sulfide solid electrolyte and composite positive electrode material as described in claim 6.

Citation Information

Patent Citations

  • Alloy / carbon composite film for all-solid-state battery and preparation method of alloy / carbon composite film

    CN115763706A

  • Sulfide all-solid-state battery and preparation method thereof

    CN117154012A